Optimalisasi Pembibitan Kentang di Greenhouse dengan Teknologi IoT Berbasis Sensor NPK - Ade Ismail; Vipkas Al Hadid Firdaus; Kadek Suarjuna Batubulan; Luqman Affandi (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2026)
This study aims to design and implement an Internet of Things (IoT)-based Smart Precision Farming system to optimize potato seedling cultivation through precise and efficient nutrient management. The system is developed using a dual-node ESP32 microcontroller architecture for real-time microclimate data acquisition and soil NPK level monitoring using an industrial-grade sensor with the RS485 Modbus communication protocol. The automated fertigation strategy is implemented using Mamdani Fuzzy Logic integrated with MQTT, Node-RED, and Grafana platforms for data visualization. Technical performance evaluation reveals high system reliability, with a Mean Absolute Percentage Error (MAPE) of 2.62% for the NPK sensor and actuator response latency of <500 ms. Greenhouse implementation proves that transitioning from schedule-based to demand-based fertilization significantly increases fertilizer efficiency by up to 30.3%. This reduction in fertilizer volume does not trigger nutrient deficiency but instead optimally stimulates the agronomic growth of potato seedlings (Sig. < 0.05), indicated by a 15.9% increase in plant height and a 33.3% increase in the number of leaves. The application of this technology offers a concrete and measurable solution to minimize fertilizer waste while improving growth quality in the horticultural seedling phase.